On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae) - Sankaran, Pradeep M.; Malamel, Jobi J.; Joseph, Mathew M.; Sebastian, Pothalil A. (Zootaxa, 2017)
The tetragnathid spider genus Tylorida Simon, 1894 is reviewed in India. The relationship of Tylorida with Orsinome Thorell, 1890 is discussed and illustrated. The taxonomic significance of male chelicerae of Tylorida spp. is discussed and an identification key based on the features of male chelicerae to separate Indian Tylorida spp. is provided. A new species, Tylorida flava sp. nov. is described and illustrated. Two new transfers and four new synonyms are proposed: Orsinome marmorea Pocock, 1901 and Tylorida culta (O. Pickard-Cambridge, 1869) are transferred to Tylorida and Mesida Kulczyn’ski, 1911 respectively, Tylorida cylindrata (Wang, 1991) and Tylorida sataraensis Kulkarni, 2014 are synonymised with Tylorida marmorea (Pocock, 1901) comb. nov., Tylorida nicobarensis (Tikader, 1977) is synonymised with Tylorida striata (Thorell, 1877) and Leucauge pondae Tikader, 1970 is synonymised with Tylorida ventralis (Thorell, 1877). The biology, natural history and intraspecific variations of T. marmorea comb. nov. are noted. The occurrence of intraspecific variations and colour polymorphism in T. ventralis is discussed and two colour morphs (Silver and Yellow morphs) and three varieties (varieties I, II & III) for the species are recognised. Additionally, the genus Atelidea Simon, 1895 is recorded for the first time from India and provided the description and illustration of Atelidea nona sp. nov.. The current distribution of Atelidea is mapped.